Information Communication Technology (ICT) use for information access by visually and physically impaired persons in public university libraries in Kenya - Kiruki, Beatrice Wamaitha; Mutula, Stephen Mudogo (International Journal of Knowledge Content Development & Technology, 2023)
This article is a spinoff of a doctoral study that was completed at the University of KwaZulu-Natal (South Africa) in 2018 on provision of information services to persons with visual and physical impairments in public university libraries in Kenya. The article examined how ICTs such as internet, e-resources and e-databases, word processing, websites and more were being used in public university libraries to provide access to information by visually and physically impaired persons. Data were collected from the visually and physically impaired students, University Librarians, Systems librarians, staff from disability departments and library staff who provided services to visually and physically impaired persons. The findings revealed that the visually and physically impaired persons in most of the libraries could not access information owing to lack of the necessary assistive and adaptive technologies and weak institutional support and framework. The study recommend that the libraries improve assistive technology infrastructure, embrace new assistive technologies such as telepresence robots, virtual realities and more, and put in place enabling policies and capacity building programmes for library staff to enable them to provide services to persons with impairments.